PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA PAKAIAN BEKAS IMPOR DI PASAR LERENG KOTA BUKITTINGGI - Maria Magdalena; Musthafa Musthafa (LP2M Universitas Bina Bangsa, 2023)
This study has a problem formulation namely whether product quality and price have a significant effect on consumer satisfaction on imported used clothing in the Pasar Lereng Bukittinggi. This study aims to prove the relationship between the effect of product quality and price on consumer satisfaction on imported used clothing at the Lereng Market, Bukittinggi City. This type of research is quantitative research. In this study, the number of samples was 96 respondents. The data was collected using a questionnaire and the sampling technique was carried out by random sampling technique, namely sampling based on the random. The data analysis technique used is multiple regression analysis and to test the hypothesis using statistical t test. The results showed that product quality had a significant partial effect on consumer satisfaction on imported used clothing at the Bukittinggi Lereng Market. The quality of the product has a t count of 9.662 > t table 1.9858 or a sig value. is 0.000 < 0.05. Price has a significant partial effect on consumer satisfaction on imported used clothing at the Bukittinggi Lereng Market. The price has t count 2.478 > t table 1.9858 or sig value. is 0.015 < 0.05